AN ANALYSIS OF THE ROLE OF SANCTIONS IN DEVELOPING POLITENESS CHARACTER IN GRADE IV STUDENTS AT SD NEGERI WATES 2 - Nabila, Nadya Marell; Situmeang, Widia Aprilia; Susanti , Putri Anisa; Listia , Dian; Kiptiyah, Siti Maryatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2025)
Education plays a vital role in human life, continuing throughout an individual's lifetime, with character education serving as a critical focus in the learning process. This study investigates the role of teachers and schools in cultivating politeness among Grade IV students at SD Negeri Wates 2. Using a qualitative descriptive approach, data were collected through questionnaires, interviews, and document analysis. The findings reveal that teachers act as role models, instill politeness values, provide guidance, and enforce firm consequences when necessary. Meanwhile, schools support these efforts by educating parents, implementing character development programs, and fostering close collaboration among stakeholders. The study highlights the comprehensive approach required to develop politeness, combining the efforts of teachers, schools, and parents. This collaboration ensures a consistent and supportive environment for character building. The results emphasize the importance of integrating values-based education into daily school activities, aiming to shape students into individuals with strong, positive character traits. The impact of this research underscores the need for schools to prioritize character education as part of their holistic approach to student development. This study contributes to the discourse on character education by offering practical insights into strategies that effectively foster politeness among elementary school students.